Dissecting the Role of Subtypes of Gastrointestinal Vagal Afferents - Wang, Yoko B.; de Lartigue, Guillaume; Page, Amanda J. (Frontiers in Physiology, 2020)
Gastrointestinal (GI) vagal afferents convey sensory signals from the GI tract to the brain. Numerous subtypes of GI vagal afferent have been identified but their individual roles in gut function and feeding regulation are unclear. In the past decade, technical approaches to selectively target vagal afferent subtypes and to assess their function has significantly progressed. This review examines the classification of GI vagal afferent subtypes and discusses the current available techniques to study vagal afferents. Investigating the distribution of GI vagal afferents subtypes and understanding how to access and modulate individual population are essential to dissect their fundamental roles in the gut-brain axis.